Resource use productivity and efficiency in maize production in farm settlements of western Nigeria - ADESIMI, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The economics of resource-use productivities and efficiency in maize production were examined among selected farm settlers in western Nigeria. Using the production function approach, it was found that resource productivities fluctuated from year to year and substantial resource dis-equilibria also existed. Measures, designed to make the needed adjustments are discussed